The pattern and distribution of malignancies reported in Hadhramout Sector, Yemen – 2002-2011 - Badheeb, Ahmed Mohamed (Author (مجلة الأندلس للعلوم الاجتماعية والتطبيقية, 2023)
The pattern and distribution of malignancies reported in Hadhramout Sector, Yemen – 2002-2011